2023
DOI: 10.1007/s11469-023-01054-6
|View full text |Cite
|
Sign up to set email alerts
|

Are Cyberchondria and Intolerance of Uncertainty Related to Smartphone Addiction?

Abstract: Smartphones are a medium for performing online activities, and one such activity could be the compulsive online health information search — cyberchondria. This study aimed to test whether cyberchondria and intolerance of uncertainty (IU) positively predict smartphone addiction (SA), adjusted for age, gender, daily use duration, the reason for using smartphones, and symptoms of anxiety and depression. The sample consisted of 471 adults (55.2% women) from the general population without chronic diseases (Mage = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Another study [ 86 ] found that intolerance of uncertainty strongly predicts problematic smartphone use a month later. Both high intolerance of uncertainty and cyberchondria have been found to predict SPA [ 26 ]. Moreover, the emotional response to uncertainty is the key reason SPA results from intolerance of uncertainty [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study [ 86 ] found that intolerance of uncertainty strongly predicts problematic smartphone use a month later. Both high intolerance of uncertainty and cyberchondria have been found to predict SPA [ 26 ]. Moreover, the emotional response to uncertainty is the key reason SPA results from intolerance of uncertainty [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that a person's intolerance of uncertainty mediated the relationship between their capacity to control their emotions and their fear of being unable to use their smartphone [ 25 ]. People who have a strong aversion to uncertainty and engage in excessive usage of smartphones may develop SPA, especially if they also have cyberchondria [ 26 ].…”
Section: Introductionmentioning
confidence: 99%